PEDAGOGICAL TRAINING OF FUTURE TEACHERS THROUGH A CLUSTER APPROACH DEVELOP SKILLS - Yuldosheva Gulira’no Zaripjon kizi (PEDAGOGS, 2025)
Abstract. The development of pedagogical skills of future teachers through a cluster approach is a pressing problem, and its effectiveness was analyzed in the study. The cluster approach and innovative pedagogical technologies were used as a method. According to the results, this approach has been proven to be effective in the formation and strengthening of pedagogical competencies. As a scientific and practical contribution, the author has developed proposals and methodological recommendations for developing pedagogical skills based on a cluster approach.